(untitled) (Journal of the College of Basic Education, 2022)
Training methods and methods differed in achieving good results in energy production and in preparing the bodily devices to meet the requirements of training. Therefore, the researcher sought to use training according to the anaerobic threshold as a new method that was not used by this football coach. The study aimed to:1. Develop a training program according to the anaerobic threshold2. Knowledge of the values ​​of energy production capacity variables and some biochemical variables (LA, LDH) and cortisone.3. Knowing the effect of the training program on the energy variables (aerobic and anaerobic capacities).4. Knowing the effect of the training program on the value of enzyme activity (LDH) as well as lactic acid (LA).5. Know the effect of the training program on the cortisone hormone.